What You Need to Know about Degenerative Mitral Valve Regurgitation in 2006 - Griffin, Brian; Rosenhek, Raphael; Bonow, Robert O.; Schwartz, Allan (MD Conference Express, 2006)
“Myxoid changes are the leading cause of mitral valve (MV) prolapse and regurgitation,” according to Brian Griffin, MD, Cleveland Clinic. Myxoid chordae in MR have <25% of normal load bearing capacity, Dr. Griffin noted. “But are these myxomatous changes genetically programmed or maladaptative?” Dr. Griffin asked. “More studies are needed to help answer this question”